Entanglement and feminist agency in picture books. (17th December 2019) - Netz, Hadar; Kuzar, Ron
Abstract : How are gender ideologies encoded in children's picture books recommended as non-sexist? Previous research indicates that fully reversing gender roles and creating a gender-egalitarian universe of discourse might be an unrealistic authorial endeavour. In the current study, we examine a different kind of enterprise. Having identified a group of picture books to investigate, which we define as anti-sexist (rather than non-sexist), we apply the vocabulary of critical thought elsewhere applied to class, literature, race and gender, thereby offering a critical outlook to the analysis of feminist ideologies in picture books. We show how these anti-sexist books, rather than attempting to reverse dominant gender ideologies, make their female protagonists struggle their way from within openly presented sexist realities to agentive gender subversion. This struggle involves interplay between gender stereotypical and anti-stereotypical elements in moments of entanglement, which are ultimately resolved with a victorious moment of gender-subversive agency.